Minimally invasive surgery and its integration to the inter -, trans - and multidisciplinarity processes - Miguel Licea Videaux; Roberto Santana Caballero (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: Thanks to the use of the new technologies and the goodness of minimally invasive surgery, as well as its application to other specialties, it has been possible to reach a new approach of health problems. The positive effect of the inter -, trans - and multidisciplinarity processes in all the branches of medical sciences is an undeniable true.  Objective: To analize critically the relationship between minimally invasive surgery and its integration to the inter -, trans - and multidisciplinarity processes.  Methods: A documental study of review articles, series and cases reports in English and Spanish, was carried out from January, 2008 to December, 2021, in Cuban and foreign journals with indexation in recognized databases.  Development: The relationship between the laparoscopic surgery and the inter -, trans - and multidisciplinarity processes was analized.  Conclusions: The minimally invasive surgery is involved in the inter -, trans - and multidisciplinarity processes in its daily performance for the solution of health problems.